Advice to a Mother on the Management of Her Children - Chavasse, Pye Henry, 1810-1879 (Salt Lake City, UT : Project Gutenberg, 2004)
"Advice to a Mother on the Management of Her Children" by Pye Henry Chavasse is an instructional guide focused on the care and upbringing of children, likely written in the late 19th century. The book provides crucial insights and practical advice for mothers, emphasizing the importance of knowledge in effectively managing the health and well-being of their offspring. The opening of the book sets a conversational tone, as the author offers to share his expert advice on essential topics related to child management, including health maintenance, recognizing symptoms of illnesses, and emergency treatments when medical assistance is not readily available. Chavasse highlights that the significant responsibility of childcare predominantly falls on mothers, urging them to educate themselves to avoid mishaps. He addresses various aspects of infant care in the first part, such as proper washing techniques, management of the navel, and the significance of cleanliness, underscoring that diligent care during infancy lays a strong foundation for a child$1 (Bs overall health and development. (This is an automatically generated summary.)s
Release date is 2004-09-01
Produced by Charles Aldarondo, Charles Franks, Arno Peters and the Online Distributed Proofreading Team
Keywords: Child care; Children -- Health and hygiene; Infants -- Health and hygiene